The Effect of Mudharabah Deposits and Wadiah Savings on the Profitability of BSI - Nesya Aulia; Laylan Syafina; Nurwani Nurwani (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study analyzes the effect of Mudharabah Deposits and Wadiah Savings on the profitability of Bank Syariah Indonesia (BSI) for the 2021–2024 period, measured using Net Profit Margin (NPM). A quantitative approach with multiple linear regression was applied to 46 monthly observations (after outlier removal) from BSI official financial reports, with classical assumption tests conducted prior to hypothesis testing. Results show that Mudharabah Deposits have a positive and significant partial effect on profitability (t = 3.198; sig. = 0.003), as profit-sharing-based funds expand financing capacity and income generation. Wadiah Savings also exhibit a positive and significant partial effect (t = 7.131; sig. < 0.001), reflecting their role as low-cost funds that enhance cost efficiency and profit margins. Simultaneously, both variables significantly influence profitability (F = 147.172; sig. < 0.001), with a strong coefficient of determination (R² = 0.873), indicating that 87.3% of NPM variation is explained by these variables. These findings confirm that an optimal combination of profit-sharing and low-cost funding structures is critical to sustainable Islamic bank profitability. Note that the high R² may partly reflect the limited scope of the model; future studies should incorporate additional variables such as NPF, BOPO, and CAR.